(3JhVjM GdeHge Ydi eJf GdSdes - (3eMeO Hf jhSa Hf EHQGgje GdaQbis; (3YHO GdQMef GdeGdcj GdGNVQjs ((3YHO GdbGOQ GdZSGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd efWb GdYdeGA SdekG dPhi GdCagGe hHYO ajbhd GdabjQ eMeO GdaQbi gPG TQM dWja Ydi eJf GdSde EfJNHJg ef TQM eDdag YHO GdQMef GdeGdci GdCNVQi hef TQM GdTjN CMeO GdOefghQi s
(3BNQgG (B:s
(3hcGf GdaQGZ ef JCdja gPG GdTQM BNQ jhe ef QLH SfI Cda heGFI hSHY hJSYjf hbO Sgd Gddg JCdjag ai eOI jSjQI HGdfSHI dfG afSCdg Cf jSgd dfG CehQfG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJH GdeJf HeOGO CMeQ hcJH GdTQM HeOGO CShO s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdadSaI hGdefWbs